2021 43rd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2021
DOI: 10.1109/embc46164.2021.9630909
|View full text |Cite
|
Sign up to set email alerts
|

Brain Light-Tissue Interaction Modelling: Towards a non-invasive sensor for Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one of the leading causes of death worldwide, yet there is no systematic approach to monitor TBI non-invasively. To the aim of developing a novel optical sensor for TBI monitoring, this paper presents a Monte Carlo model of optical interaction with healthy human head to optimize the sensor geometry. Investigation with a range of source-detector separations at a near-infrared optical window reveals that maximum light is absorbed in the skull and the minimum interaction takes plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This characteristic enables the extraction of an optical signal that is independent of blood oxygenation ( Murkin and Arango, 2009 ). Montecarlo simulation of the light-tissue interaction has demonstrated that near-infrared (NIR) light travels deeper into the head tissue when the source-detector distance is increased ( Roldan et al, 2021 ). The reflected light from extracerebral tissue reached the proximal photodetector placed 10 mm from the LEDs; and the non-absorbed light from deeper tissues travelled back to the distal photodiode placed 35 mm from the LEDs.…”
Section: Methodsmentioning
confidence: 99%
“…This characteristic enables the extraction of an optical signal that is independent of blood oxygenation ( Murkin and Arango, 2009 ). Montecarlo simulation of the light-tissue interaction has demonstrated that near-infrared (NIR) light travels deeper into the head tissue when the source-detector distance is increased ( Roldan et al, 2021 ). The reflected light from extracerebral tissue reached the proximal photodetector placed 10 mm from the LEDs; and the non-absorbed light from deeper tissues travelled back to the distal photodiode placed 35 mm from the LEDs.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is the perfect point to record an optical signal independent of blood oxygenation that could be correlated to intracranial volumetric changes. Moreover, as explained in a previous Monte Carlo simulation paper [46], a higher source-detector (S-D) distance allows light to travel deeper into the tissue; hence, pulsatile signals from a photodiode located at 2.8 mm should relate to volumetric information from the cerebral tissue. The optical signal was acquired through an in-house instrumentation system connected to a NI DAQ for analogueto-digital conversion.…”
Section: Signal Acquisition Systemmentioning
confidence: 99%
“…Previous evaluation of infrared light and cerebral tissue interaction at different sourcedetector (S-D) separations showed that higher S-D separation increases the penetration depth, but it also causes a decrease in the overall signal quality due to high absorption [21]. Accordingly, the probe design was subdivided into two individual sub-probes called proximal probe and distal probe (Figure 1).…”
Section: Optical Partsmentioning
confidence: 99%